1989
DOI: 10.1007/bf00187063
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of a vortex ring interacting with an inclined wall

Abstract: An experimental study has been made on the interaction of a vortex ring with a plane solid boundary which is inclined to the axis of the ring. Dye visualizations of the ring during the interaction revealed (i) the formation of bi-helical vortex lines around the circumferential axis of the ring, and (ii) that these vortex lines were constantly being displaced along the circumferential axis on either side of the plane of symmetry and towards the region of the ring furthest away from the wall. Key factors which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 14 publications
6
63
0
Order By: Relevance
“…To demonstrate that the algorithm is robust enough to handle more complex problems, we also computed an adaptive solution for a viscous vortex ring merger problem, similar to the ones studied computationally in [2,4,17] and experimentally in [5,18]. The initial conditions are two vortex rings which are angled toward each other by an inclination angle φ from horizontal.…”
Section: Vortex Merger Examplementioning
confidence: 99%
“…To demonstrate that the algorithm is robust enough to handle more complex problems, we also computed an adaptive solution for a viscous vortex ring merger problem, similar to the ones studied computationally in [2,4,17] and experimentally in [5,18]. The initial conditions are two vortex rings which are angled toward each other by an inclination angle φ from horizontal.…”
Section: Vortex Merger Examplementioning
confidence: 99%
“…Smoke is introduced uniformly around the circumference of the tube only, and a thin laser sheet is used to illuminate the flow. (a) Depicts the formation of the shear layer vortices and (b) shows the process of vortex tripling (Lim, 1989). It is suggested that Mode A is an "elliptic" instability of the cores, and Mode B is a "hyperbolic" instability of the braid vorticity.…”
Section: End View Oblique Viewmentioning
confidence: 99%
“…The Reynolds number of the flow based on the initial velocity and the diameter of the nozzle is about 600. Note how differential vortex stretching has led to the formation of hi-helical vortex lines (see (c)) which are constantly being displaced along the circumferential axis and towards the region of the ring furthest away from the wall (Lim, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of laboratory experiments have been performed to study the interaction of two vortex rings moving side by side in the same direction [58][59][60][61][62][63]. As time proceeds, the rings are drawn together and they merge into a single ring that later splits apart again into two rings.…”
Section: Vortex Ring Mergermentioning
confidence: 99%